2009
DOI: 10.2214/ajr.08.1283
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Percutaneous Imaging-Guided Biopsy of Peritoneal and Omental Masses: Results in 111 Patients

Abstract: Percutaneous imaging-guided biopsy of peritoneal and omental masses is a safe, effective procedure that is useful in clinical practice. A second malignancy was revealed in a substantial number of patients with a known primary cancer. A new malignancy was diagnosed in most patients without a history of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 12 publications
5
45
0
5
Order By: Relevance
“…The technique has been extensively used to biopsy the bile duct, gallbladder [6,7] , hepatic hilum [8] , regional lymph nodes [9] pancreatic lesions [10] and hepatic lesions [11] as well as for aspiration of malignant ascites [12] . CT guided FNA has been utilized to biopsy peritoneal and omental masses [13] . This case also delineates the difficulties encountered while managing patients with cholangiocarcinoma and cirrhosis [14,15] .…”
Section: Discussionmentioning
confidence: 99%
“…The technique has been extensively used to biopsy the bile duct, gallbladder [6,7] , hepatic hilum [8] , regional lymph nodes [9] pancreatic lesions [10] and hepatic lesions [11] as well as for aspiration of malignant ascites [12] . CT guided FNA has been utilized to biopsy peritoneal and omental masses [13] . This case also delineates the difficulties encountered while managing patients with cholangiocarcinoma and cirrhosis [14,15] .…”
Section: Discussionmentioning
confidence: 99%
“…The usual contraindications to biopsy are abnormal hemostasis, gaseous distention, or lack of patient cooperation. Complications are rare (2-3%) [44] and usually well tolerated. There is a risk of intestinal perforation, but it is usually of little consequence due to the small caliber of the biopsy needle.…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…While the specificity of needle biopsy to determine malignancy is excellent (100%), the sensitivity is considerably weaker (89-95%) [43,46]. Some authors propose that if a biopsied lesion is labelled as ''benign'' but without a specific etiologic diagnosis, the patient should undergo repeat biopsy [44]. When a difficultly-placed mass is inaccessible to percutaneous biopsy or if radioguided biopsy fails to yield a diagnosis (4% of cases according to Gottlieb et al [47]), surgical biopsy by either laparoscopy or open laparotomy is the next option.…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…In another study of 111 percutaneous image-guided peritoneal and omental biopsies, the overall diagnostic rate was 89%, with a sensitivity of 93% and specificity of 86% [26]. Moreover, the authors concluded that a second malignancy was revealed in approximately 10% of patients with a known primary cancer (8/79), such as non-Hodgkin’s lymphoma [27]. …”
Section: Role Of Image-guided Biopsymentioning
confidence: 99%